Abundance of carbapenemase genes (blaKPC, blaNDM and blaOXA-48) in wastewater effluents from Tunisian hospitals. (October 2017) - Nasri, Emna; Subirats, Jessica; Sànchez-Melsió, Alexandre; Mansour, Hedi Ben; Borrego, Carles M.; Balcázar, José Luis
Abstract: Carbapenems are β-lactam antibiotics with a broad spectrum of activity and are usually considered the last resort for the treatment of severe infections caused by multidrug-resistant pathogens. The clinically most significant carbapenemases are KPC, NDM, and OXA-48-like enzymes, whose genes have been increasingly reported worldwide in members of the family Enterobacteriaceae . In this study, we quantified the abundance of these genes in wastewater effluents from different Tunisian hospitals. The bla NDM and bla OXA-48 -like genes were detected at similar concentrations in all hospital wastewater effluents. In contrast, the bla KPC gene was detected at lower concentration than other genes and it was only detected in three of the seven effluents analyzed. To the best of our knowledge, this study quantified for the first time the abundance of bla KPC, bla NDM, and bla OXA-48 -like genes in wastewater effluents from Tunisian hospitals, highlighting the widespread distribution of these carbapenemase genes. Graphical abstract: Highlights: Abundance of carbapenemase genes in Tunisian hospital effluents was monitored. The bla NDM and bla OXA-48 -like genes were detected at similar concentrations in all hospital wastewater effluents. The bla KPC gene was detected at lower concentration than other carbapenemase genes. Abstract : Wastewater effluents from Tunisian hospitals are a potential source of carbapenemase genes, with the bla NDM and bla OXA-48 -like genes being the most predominant.